2022
DOI: 10.1007/s12144-021-02591-w
|View full text |Cite
|
Sign up to set email alerts
|

Cross-level effects of health-promoting leadership on nurse presenteeism: The mediation and moderation effect of workload and performance pressure

Abstract: This study examines the cross-level influence mechanism of leaders’ health-promoting leadership on subordinates’ presenteeism among nursing industry. A multilevel mediated moderation model was hypothesized to explore whether health-promoting leadership is associated with subordinates’ presenteeism via the workload of subordinates, and how leader’s performance pressure plays the role in the model. Questionnaires were distributed to 110 nursing teams, which including 110 chief nurses and 660 subordinate nurses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
(70 reference statements)
0
9
0
2
Order By: Relevance
“…Moreover, the impact of leadership on subordinates' behaviors is also noticeable in that leadership would likely play a vital role in shaping the healthy work behaviors of subordinates. Limited empirical research showed that health-promoting leadership and supportive leadership behavior were conducive for reducing the incidence of employees' presenteeism [15,16]. From the theory of paternalistic leadership [17], the work team is analogous to a family in which a leader acts as the father with two typical characteristics, majesty and mercy, while the subordinates play the role of a child, thereby reflecting the concept of "superior and inferior" in traditional Chinese culture.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the impact of leadership on subordinates' behaviors is also noticeable in that leadership would likely play a vital role in shaping the healthy work behaviors of subordinates. Limited empirical research showed that health-promoting leadership and supportive leadership behavior were conducive for reducing the incidence of employees' presenteeism [15,16]. From the theory of paternalistic leadership [17], the work team is analogous to a family in which a leader acts as the father with two typical characteristics, majesty and mercy, while the subordinates play the role of a child, thereby reflecting the concept of "superior and inferior" in traditional Chinese culture.…”
Section: Introductionmentioning
confidence: 99%
“…En consecuencia, las intervenciones para el manejo del estrés en el personal de enfermería deberán enfocarse en la prevención de la enfermedad y el mantenimiento de la salud psicofísica asociada al EO. Para esto se deben implementar mecanismo de control, que intervengan los obstáculos en la ejecución de tareas relacionados con el estrés, (24) como: manuales de funciones claros; horarios y volumen de trabajo establecidos sin sobrecarga; y líderes con Garnica Serrano EA , et al formación sólida en motivación personal.…”
Section: Discussionunclassified
“…Estas recomendaciones son consistentes con evidencia previa en la que se identificó que la presión y la sobrecarga laboral, ejercida y asignada por los líderes del personal de enfermería, tiene mayor incidencia en el porcentaje de presentismo y perdida de actividad. (24) Por esta razón, resulta oportuno propiciar ambientes laborales de comunicación, diálogo y confianza entre todos los miembros de la organización, sin importar el papel que desempeñen dentro de ella. (23,26) Limitaciones: este es un estudio correlacional transversal.…”
Section: Discussionunclassified
“…What this obligation and/or volunteering means are the requirements and motivations behind the decision to presenteeism. Indeed, research on presenteeism has shown that compelling or motivating factors such as public service motivation (Deng et al, 2019), organisational culture (Ruhle & Süß, 2020), nature of work (Caverley et al, 2007;MacGregor et al, 2008;Veale et al, 2016), manager and colleague pressure (Baker-McClearn et al, 2010;Rebmann et al, 2016), workload (Shan et al, 2022), the difficulty of employee substitution (Aronsson & Gustafsson, 2005), and economic difficulties (Chiu et al, 2017;Hemp, 2004;Webster et al, 2019) are effective in making a presenteeism decision.…”
Section: Presenteeism Processmentioning
confidence: 99%
“…Organisational policies (Holland & Collins, 2018), pressures to participate (manager, colleague, clients) (Baker-McClearn et al, 2010;Biron & Saksvik, 2009;Rebmann et al, 2016), the interdependence of tasks (Grant & Parker, 2009), fear of losing one's job (Holland & Collins, 2018), economic concerns (Aronsson & Gustafsson, 2005;Chiu et al, 2017), workload (Hansen & Andersen, 2008;Shan et al, 2022), and organisational culture (Ruhle & Süß, 2020) are widespread situations for the employee to participate in working life due to obligation (Biron et al, 2006). This situation is defined as involuntary presenteeism in the literature (Gosselin & Lauzier, 2011).…”
Section: Why Does a Person Keep Working When Unwell?mentioning
confidence: 99%